Update on Modernization Legislation - John C. Dugan (Washington University Law Quarterly, 1999)
Since 1980, eight of the ten two-year Congresses have considered major financial services reform legislation. They’ve all had varying degrees of progress, but they’ve all failed to get to the finish line for one reason or another. This commentary suggests that significant reform legislation may soon pass in Congress. This commentary describes what significant reform legislation might do for financial services.
Keywords: Financial services industry; Banking law; Deregulation; Financial institutions; Financial services; Securities law